PENGARUH RETURN ON EQUITY, EARNING PER SHARE DAN NET PROFIT MARGIN TERHADAP HARGA SAHAM PADA PT. GUDANG GARAM Tbk PERIODE 2004 – 2013 - Pupu Pupu (Universitas Batanghari Jambi, 2017)
Abstract : This study aims to determine the company's financial performance through the development of Return On Equity (ROE), Earning Per Share (EPS), Net Profit Margin (NPM) and how they affect the price of shares. Gudang Garam Tbk period 2004 to 2013.The method used is quantitative analysis method, which uses statistical formulas that are tailored to the title of the study and issues to be studied. The results showed that the development of Return On Equity (ROE), Earning Per Share (EPS), Net Profit Margin (NPM) PT. Gudang Garam Tbk during the period 2004 to 2013 is likely to fluctuate with an average growth of 4.4% ROE, EPS 16.0%, NPM of 6.3% and 46.7% share price.Results of subsequent research is ROE negatively affect the stock price with a coefficient of 7.304 influences. While EPS and NPM positive effect on the stock price with the influence coefficients respectively 1.380 and 6.310. Judging from the value of the coefficient of determination (R 2) R square of 0.772 or 77.2% variation in stock prices can be explained by the variation of the three independent variables while the rest is explained by other factors outside of the study.Keywords: Return on Equity, Earnings Per Share, Net Profit Margin, share price